Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4821996
|View full text |Cite
|
Sign up to set email alerts
|

Contact resistivity and suppression of Fermi level pinning in side-contacted germanium nanowires

Abstract: Electrical properties of contact-interfaces in germanium nanowire field effect transistor devices are studied. In contrast to planar bulk devices, it is shown that the active conduction channel and gate length extend between and underneath the contact electrodes. Furthermore, direct scaling of contact resistivity and Schottky barrier height with electrode metal function is observed. The associated pinning parameter was found to be γ=0.65 ± 0.03γ=0.65 ± 0.03, which demonstrates a significant suppression of Ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…22. Our earlier studies 12,22,23 indicated that the as-grown NWs were p-type doped with carrier concentrations ranging from 3 Â 10 17 cm À3 up to 10 19 cm À3 . This behaviour is characteristic for all nonintentionally doped synthetically derived Ge NWs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…22. Our earlier studies 12,22,23 indicated that the as-grown NWs were p-type doped with carrier concentrations ranging from 3 Â 10 17 cm À3 up to 10 19 cm À3 . This behaviour is characteristic for all nonintentionally doped synthetically derived Ge NWs.…”
mentioning
confidence: 99%
“…10,11 In this manuscript, we present experiments in which implantation is carried out on an electrically side-contacted individual nanowire. 12 This has many advantages: (i) the dynamic annealing can be tracked in operandi by the electrical measurement upon ion implantation; (ii) the side contact geometry allows for doping only the conduction channel, while the buried contact is essentially unchanged; (iii) by the use of an ion implanter, any element can, in principle, be incorporated, in particular, the technologically relevant element B, and further allowing for scalable doping of integrated circuits with controlled dopant distributions and depth. This technique complements the extensive studies in the past years that targeted changes in microscopic structure after ion implantation of semiconductor NWs with full area 13,14 and focused ion beam (FIB) 15,16 techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical characterization was carried out at ambient conditions. The geometry of each NW device (diameter size and channel length) was determined by electron microscopy [11,16]. From this the NW resistivity was extracted as function of diameter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts to achieve reliable junctions in nanodevices can be considered as obtaining lower metal-metal or metal-semiconductor contact resistance. It has been reported that the contributions to contact resistance include micro-scale geometry [1][2][3][4][5], oxide layer of semiconductor materials [6,7], difference of Fermi energy between nanomaterials and electrodes [8], and contact force between two metal films [3]. Furthermore, dependence on contact force [3,9] was investigated, as well as dependence on contact length [10], to understand characteristics of contact resistance.…”
Section: Introductionmentioning
confidence: 99%